The relationship between independent learning and mathematical creative thinking ability in vocational high school students - Khair, Salsabila Nazhifatin; Suhendra, Suhendra; Nurfaizah, Nurfaizah (Universitas Maritim Raja Ali Haji, 2025)
This study contributes to mathematics education by clarifying how independent learning supports students’ creative thinking processes, particularly in vocational contexts where autonomy and problem-solving skills are crucial. This study focuses on students' learning independence and creative thinking skills with the aim of determining whether there is a relationship between learning independence and creative thinking skills among vocational high school students. This study uses a quantitative descriptive approach with a correlational method conducted at one of the vocational high schools in Tangerang City, Banten Province. The sample in this study consisted of 30 students from the 10th-grade Multimedia class. Data collection techniques included observation, a 24-item questionnaire, and a written test with 5 questions. The instruments were validated by experts and declared suitable for use, ensuring content validity and reliability. Based on the results of the study conducted in the Multimedia class, it can be concluded that the level of learning independence and creative thinking ability of students is above average, with 13 students (43.33%) scoring below average and 17 students (56.66%) scoring above average, and further analysis shows a strong positive correlation (r = 0.970, p < 0.01) between the two variables. Based on the hypothesis test, there is a significant relationship between learning independence and students' creative thinking ability.